2009
DOI: 10.1021/jp809401r
|View full text |Cite
|
Sign up to set email alerts
|

Small Copper Clusters in Ar Shells: A Study of Local Structure

Abstract: Small copper clusters embedded in argon shells were obtained using the pick-up technique. The clusters were analyzed using X-ray absorption near-edge spectroscopy (XANES) measured at the Cu L 23 -edge. Theoretical interpretation of the experimental spectra has been performed using full-potential finite difference method simulations and density functional theory (DFT) to optimize the geometry of the clusters. As a result, it was found that the icosahedral Cu 13 nanocluster with the geometry optimized by DFT pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
(83 reference statements)
2
18
0
Order By: Relevance
“…Analysis based on constructing 3D NP structure models is especially attractive for XANES because path-by-path approaches are not applicable in this spectral region. Like EXAFS, XANES data can also be used to validate DFTgenerated 3D structure models (135,136). Likewise, the influence of atomic thermal motion on XANES spectra can be modeled by MD simulations (111,137).…”
Section: Ac12ch03_frenkelmentioning
confidence: 99%
“…Analysis based on constructing 3D NP structure models is especially attractive for XANES because path-by-path approaches are not applicable in this spectral region. Like EXAFS, XANES data can also be used to validate DFTgenerated 3D structure models (135,136). Likewise, the influence of atomic thermal motion on XANES spectra can be modeled by MD simulations (111,137).…”
Section: Ac12ch03_frenkelmentioning
confidence: 99%
“…Taking copper as an example, which contrasts with a more positive SEP metal such as gold, most previous studies focused on special cases with a stabilization mechanism such as weakly interacting environments ( e.g. , solid argon) 11 12 or strongly interacting ligation. In fact, in our previous work on Cu 13 NCs prepared by wet chemistry in a microfluidic cell 13 , rapid reduction, particularly at elevated temperature, led to an immediate nucleation of monomers and subsequent growth.…”
mentioning
confidence: 99%
“…6(a)), and the structures of 7-atom clusters, predicted to be of pentagonal bipyramidal shape, and 13-atom cluster icosahedral structures, also agree. In the work of Zhang et al 51 melting behaviour investigation of copper clusters of N = 51-56 using MD calculations is performed. It is reported that under 450 K the expected structure of these medium-sized clusters is characterized by the existence of four-shell icosahedral structure (the perfect icosahedron is predicted for cluster consisting of 55 copper atoms, corresponding to the magic number).…”
Section: Coppermentioning
confidence: 99%